Analysis of the factors that affect job satisfaction in AB Bank Limited : scenario of Garib-E-Newaz branch - Shemin, Fariya Akther (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.